Primary education, a priority factor of popular education - Luiza Lenuța AXINTE; Nicolae SILISTRARU (Acta et Commentationes, Sciences of Education, 2025)
The article analyzes the role of family education as a foundation of folk culture among primary school students, highlighting the importance of traditions and folk education in personality development. The family is seen as an essential environment for transmitting cultural and social values. A study conducted on 50 parents of primary school students in Braila County reveals a low level of knowledge about folk education, but also a strong desire to deepen their understanding of the topic. Parents request educational support and the organization of cultural activities to promote traditions. The conclusion emphasizes the need for greater parental involvement in preserving folk values.